2018
DOI: 10.1088/1361-6579/aab9de
|View full text |Cite
|
Sign up to set email alerts
|

Objective profiling of varied human motion based on normative assessment of magnetometer time series data

Abstract: By using multi-dimensional analysis of similarity measures between participants rather than direct parameterisation of the physiological data, complex and varied patterns of physical motion can be quantified, allowing objective and robust profiling of relative function across participant groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Pervasive technologies, such as accelerometers, inertial measurement units and magnetometers, have been used with reasonable success. In the study of Barnes et al [94], a magnetometer (which measures the direction, strength, or relative change of a magnetic field at a given location) was worn during a MC assessment. Using robust machine learning, data was subsequently processed, yielding visualizations of the relative performance in three-dimensions and a relative distance between children within the multidimensional scaling that could be used to create an automated sensor-based rank scoring, resulting in good agreement between observer and sensor scores.…”
Section: What We Knowmentioning
confidence: 99%
“…Pervasive technologies, such as accelerometers, inertial measurement units and magnetometers, have been used with reasonable success. In the study of Barnes et al [94], a magnetometer (which measures the direction, strength, or relative change of a magnetic field at a given location) was worn during a MC assessment. Using robust machine learning, data was subsequently processed, yielding visualizations of the relative performance in three-dimensions and a relative distance between children within the multidimensional scaling that could be used to create an automated sensor-based rank scoring, resulting in good agreement between observer and sensor scores.…”
Section: What We Knowmentioning
confidence: 99%
“…In particular, Table 1 outlines solutions proposed for quantitative activity monitoring, considering both product and process-oriented approaches, while Table 2 refers to quantitative motion analysis, which is a detailed process-oriented description of specific motor tasks. Magnetometer (Barnes et al, 2018); Force sensitive resistor (Xiao and Menon, 2014) Dynamic time warping (Barnes et al, 2018); contour mapping (Barnes et al, 2018); Extreme learning machine classifier (Xiao and Menon, 2014) Daily living Visual; time parameters; space parameters Electro-oculography (Bulling et al, 2011); gyroscope (Leutheuser et al, 2013); Radio frequency identification (RFID) (Spinney et al, 2015) Support vector machine (Bulling et al, 2011;Leutheuser et al, 2013); k-Nearest Neighbor classifier (Leutheuser et al, 2013); classification and regression tree (Leutheuser et al, 2013); linear correction (Spinney et al, 2015) PA intensities Visual; tangible; frequency parameters…”
Section: A Synthetic Out-line Of the State Of The Art: A Brief Overvi...mentioning
confidence: 99%
“…Whilst Barnes et al (Barnes et al, 2018) show that comparison of an automated, sensor-based method to the standard approach has a strong correlation to subjective human-assessed scores.…”
Section: Movement Componentmentioning
confidence: 99%
“…Recently there have been developments in technological and analytical capability, permitting the quantification of complex human movement behaviours (Clark, Barnes, Stratton, et al, 2016) which have as yet untapped potential to be applied to the assessment of motor competence. Pervasive technologies, such as accelerometers, inertial measurement units and magnetometers have been used, albeit in only a small number of studies, with reasonable success to automatically assess and score motor competence (Barnes, Clark, Rees, Stratton, & Summers, 2018;Bisi, Panebianco, Polman, & Stagni, 2017). For example, Barnes et al (2018) demonstrated good agreement between observer and magnetometry derived motor competency scores, where raw tri-axial magnetometer traces underwent pattern recognition and were systematically compared against human-assessed scores, with correlation coefficients of the overall score in the range of 0.62-0.71 for different cohorts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation